2022
DOI: 10.1021/acs.jafc.2c02798
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on the Preparation and Application of Ionic Amphiphilic Lignin: A Comprehensive Review

Abstract: As the second most abundant natural polymer after cellulose, lignin has received considerable attention recently due to its reproducibility, safety, and biodegradability. Studies are now focusing on the development of new lignin applications to replace petroleum-based chemicals. Unfortunately, lignin has several inherent problems, such as poor water solubility and a tendency to agglomerate. However, after chemical modification, lignin can gain new functions through the introduction of new functional groups. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Although there is potential for direct industrial application, unmodified lignin can only be incorporated in small amounts due to its weak mechanical properties. On the other hand, lignin can be chemically modified to be used as a starting material for polymer synthesis or for conversion into chemicals and fuels [75][76][77][78]. There are four different ways to chemically modify lignin: (1) lignin depolymerization or fragmentation, using lignin as a carbon source or cleaving it into small fragments containing aromatic rings; (2) modification of lignin by synthesis of new chemically active sites; (3) chemical modification of the hydroxyl groups presents in the lignin structure; and (4) production of graft copolymers.…”
Section: Biomass-based Materials Optimizationmentioning
confidence: 99%
“…Although there is potential for direct industrial application, unmodified lignin can only be incorporated in small amounts due to its weak mechanical properties. On the other hand, lignin can be chemically modified to be used as a starting material for polymer synthesis or for conversion into chemicals and fuels [75][76][77][78]. There are four different ways to chemically modify lignin: (1) lignin depolymerization or fragmentation, using lignin as a carbon source or cleaving it into small fragments containing aromatic rings; (2) modification of lignin by synthesis of new chemically active sites; (3) chemical modification of the hydroxyl groups presents in the lignin structure; and (4) production of graft copolymers.…”
Section: Biomass-based Materials Optimizationmentioning
confidence: 99%
“…[23] As a green polymer with amphiphilic (hydrophilic and lipophilic) structure, lignin has good dispersing properties, and its application as a green dispersant in the field of anti-corrosive coatings has been reported in a few works. [24][25][26] Wang et al [9] exploited the non-covalent interaction between lignin and graphene to effectively improve the dispersion and stability of composites in aqueous epoxy. In our previous study, we found that sodium lignosulfonate (LS) can provide certain corrosion inhibition properties for carbon steel.…”
Section: Introductionmentioning
confidence: 99%